RISK CONTROL OF CONTINGENCY TRANSACTION IN PROFIT SHARING SYSTEM - Muhammad Rum; Kamaruddin Kamaruddin (Jurnal Iqtisaduna, 2019)
This study is descriptive and theoretical to anticipate the occurrence of losses arising from the contingency conditions in the services of sharia banks that implement the system for the results. The accounting treatment according to Ariani (2012) in the implementation of the principle of profit sharing is not fully in accordance with the principles of Islamic sharia. The compliance on the Statement of Financial Accounting Standard (SFAS) No.59 concerning Islamic banking financial accounting of the science, but there are not yet according to science Fiqh Syafi'iyah, because SAK is made for businesses that are full profit oriented while sharia principles are oriented to profit and mutual interest. Another thing that arises is the risk of uncertainty in the form of contingencies. Contingent transactions have not affected the position in the company's balance sheet and profit and loss. Contingencies under PSAK No.31 must be presented in such a way that when associated with assets and liabilities items can adequately represent the bank's financial position. Contingency is a transaction that has not changed the position of the bank's assets and liabilities at the report date, but the must be executed by the bank if the terms agreed with the customer are met.  The result in, the contingent impacts may be claims or liabilities in both Rupiah and Foreign Currency. For that reason, banks need to make capital reserves derived from income, profit, general analysis of funding, and reserves of special purpose to anticipate contingent conditions that occurred, and be borne by the bank concerned